2016
DOI: 10.1038/srep24562
|View full text |Cite
|
Sign up to set email alerts
|

Naringin ameliorates bone loss induced by sciatic neurectomy and increases Semaphorin 3A expression in denervated bone

Abstract: Naringin maintains bone mass in various osteoporosis models, while its effect on bone in disuse osteoporosis has not been reported. The present study explores whether naringin can prevent disuse osteoporosis induced by unilateral sciatic neurectomy (USN) and whether the Semaphorin 3A-induced Wnt/β-catenin signalling pathway is involved in the osteoprotection of naringin. Naringin dose-dependently prevented the deterioration of bone mineral density (BMD), trabecular structure and biomechanical strength in femur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 44 publications
2
46
1
1
Order By: Relevance
“…They found that Sema3A beneficially contributed to bone volume, bone-to-implant contact ratio and the maximal push-out force by improving peri-implant bone implant, osseointegration and fixation. Similarly, Ma et al demonstrated that naringin, the main active constituent of citrus fruits, improved bone development through increasing Sema3A expression and regulation of Wnt/β-catenin signaling [26, 27]. Clinically, Sema3A and its receptor plexin A2 is positively associated with osteocalcin [28] and BMD [29] in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…They found that Sema3A beneficially contributed to bone volume, bone-to-implant contact ratio and the maximal push-out force by improving peri-implant bone implant, osseointegration and fixation. Similarly, Ma et al demonstrated that naringin, the main active constituent of citrus fruits, improved bone development through increasing Sema3A expression and regulation of Wnt/β-catenin signaling [26, 27]. Clinically, Sema3A and its receptor plexin A2 is positively associated with osteocalcin [28] and BMD [29] in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…35,38,39 It has been found to be anti-inflammatory, antidiabetic, antifibortic, antiosteoporotic, antidyslipidemic and protected against lipodystrophy and iron induced toxicity. [40][41][42][43][44] Naringin may also have protective effects on cognition and oxidative damage. 45 Naringin reduced cell viability and cell proliferation by arresting the cell cycle at the G1 phase in 5637 cells and inhibited cyclin D1/CDK4 and cyclin E-CDK2 complexes by the increased expression of p21WAF1 and activation of Ras/Raf/ERK.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonone as a plant secondary metabolites can operate as phytoestrogens and show a wide range of health beneficial effects on bone quality. Flavonoid extract increased the tibial and femoral growth and as a result improved bone length (Choudhary et al, ; Ma et al, ; Xu, Li, Wooley, Yang, & Jiang, ). Examining histomorphometry of bone showed wider distal femoral and proximal tibial growth plate, increased the number and size of hypertrophic chondrocytes with subsequent improvement of longitudinal bone growth, which helped achieving the more mineralization of bone during ageing and growing (Choudhary et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The higher doses of naringin can promote the osteoblast differentiation in contrast to osteoclast differentiation. The researchers show the activity of naringin by upregulating osteocalcin (Li, Jiang, Woole, Xu, & Yang, ; Ma et al, ) osteoblast differentiation and inhibiting activity of osteoclastogenesis by downregulating of C‐terminal telopeptides of collagen type 1 (CTX‐1) an index of bone resorption activity, in plasma (Li et al, ). These results show that flavonone like naringin can act as a potent agent in bone formation and metabolism (Mandadi et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation